Scattering of strahl electrons in the solar wind between 0.3 and 1 au: Helios observations. Issue 3 (17th April 2019) - Berčič, L; Maksimović, M; Landi, S; Matteini, L
ABSTRACT: Electron velocity distribution functions in the solar wind according to standard models consist of four components, of which three are symmetric – the core, the halo, and the superhalo, and one is magnetic field-aligned, beam-like population, referred to as the strahl. We analysed in situ measurements provided by the two Helios spacecrafts to study the behaviour of the last, the strahl electron population, in the inner Solar system between 0.3 and 1 au. The strahl is characterized with a pitch-angle width (PAW) depending on electron energy and evolving with radial distance. We find different behaviour of the strahl electrons for solar wind separated into types by the core electron beta parallel value (βec∥ ). For the low-βec∥ solar wind the strahl component is more pronounced, and the variation of PAW is electron energy dependent. At low energies a slight focusing over distance is observed, and the strahl PAW measured at 0.34 au agrees with the width predicted by a collisionless focusing model. The broadening observed for higher energy strahl electrons during expansion can be described by an exponential relation, which points towards an energy-dependent scattering mechanism. In the high-βec∥ solar wind the strahl appears broader in consistence with the high-βec∥ plasma being more unstable with respect to kinetic instabilities. Finally we extrapolate our observations to the distance of 0.16 au, predicting the strahl PAWs in the low-βec∥ solar wind to be ∼29° for all energies, and in the high-βec∥ solar wind a bit broader, ranging between 37° and 65°.